علاقة مهارات الفهم القرائي بتشتت الإنتباه وفرط الحركة لدى ذوي صعوبات القراءة - نسيب, أية; قيطون, كنزة (University of Eloued جامعة الوادي, 2021)
ملخص الدراسة: تهدف هذه الدراسة إلى معرفة العلاقة بين مستويات الفهم القرائي لذوي صعوبات القراءة بفرط الحركة وتشتت الإنتباه لدى فئة تلاميذ سنة رابعة إبتدائي وذلك بالإجابة على التساؤل الرئيسي التالي: هل توجد علاقة إرتباطية بين الفهم القرائي تشتت الانتباه وفرط الحركة؟ وقد تم الإعتماد على المنهج الوصفي لأنه الأنسب لهذه الدراسة، كما تم الاعتماد على مقياس مستويات الفهم القرائي لصاحبه الباحث أحمد حسين الدليمي، وكذلك مقياس تشتت الانتباه وفرط الحركة لصاحبه "جمال الخطيب"، وقد طبقت الأداتين على عينة بلغ عددها 70 تلميذ وتلميذة من السنة الرابعة إبتدائي في بعض ابتدائيات ولاية الوادي، وبعدها تمت المعالجة عن طريق برنامج Spssوتوصلنا في الأخير إلى: - لا توجد علاقة ارتباطية دالة إحصائيا بين الفهم القرائي تشتت الانتباه وفرط الحركة. -لا توجد فروق دالة احصائيا في الفهم القرائي تبعا لمتغير الجنس. -توجد فروق دالة احصائيا في فرط الحركة وتشتت الانتباه تبعا لمتغير الجنس. وتمت مناقشة نتائج الفرضيات اعتمادا على معلومات نظرية ودراسات سابقة كما ختمت الدراسة بخلاصة إضافة إلى قائمة المراجع وبعض الملاحق. Study summary: This study aims to find out the relationship between the levels of reading comprehension among pupils with reading difficulties with hyperactivity and attention deficit in fourth year students of primary school by answering the following main question: - Is there a correlation between reading comprehension, attention deficit and hyperactivity? The descriptive approach was relied on because it is the most appropriate for this study. The scale of reading comprehension levels of, Ahmed Hussein Al-Dulaimi was used, as well as the scale of attention-deficit hyperactivity disorder, of "Jamal Al-Khatib". The study sample was composed of 70pupils from some of the elementary schools in El-oued State, and then the treatment was done through the Spss program, and we finally reached: - There is no statistically significant relationship between reading and attention deficit hyperactivity disorder. There are no statistically significant differences in reading comprehension according to the gender variable. - There are statistically significant differences in hyperactivity and attention deficit between males and females. The results of the hypotheses were discussed based on the theoretical information and previous studies, and the study concluded with a summary in addition to a list of references and some appendices.
دراسة ميدانية على عينة من تلاميذ سنة رابعة إبتدائي – مدينة الوادي
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: الفهم القرائي، Reading comprehension، Compréhension écrite; تشتت الإنتباه، Attention Deficit,، Manque d'attention; فرط الحركة، Hyperactivity، Hyperactivité